P3.020 Prevalence of Genital Chlamydia Trachomatis and Neisseria Gonorrhoeae Infections Among Adolescents in Northern Italy. (13th July 2013) - Matteelli, A; Sulis, G; Capelli, M; Apostoli, A; Toninelli, G; D'Aversa, F Bernoni; Gargiulo, F; Salinaro, F; Castelli, F; Donato, F
Abstract : Background: Sexually transmitted infections are widespread globally, especially among people aged 15–25. Chlamydia trachomatis is the most common sexually-acquired bacterial disease. This infection is not notified in Italy; prevalence data on population-based surveys are not available. Methods: We conducted a prevalence survey among students aged 18 or older attending high schools in the Province of Brescia, Northern Italy. A total of 3134 adolescents were offered to enter the study; overall, 1886/3134 (60.2%) participated. Each consenting student answered to a socio-behavioural questionnaire and C. trachomatis and N. gonorrhoeae were searched on first void urine samples using VERSANT ® CT/GC DNA 1.0 Assay (kPCR). We present preliminary data concerning 1311 enrolled individuals attending 16 schools. Results: Overall, 63.8% (836/1311) were females and the median age was 18.4 years. Most students (91.7%) were born in Italy. 77.1% of the enrolled students declared to be sexually active (F > M, p < 0.001), with their first intercourse occurring at a median age of 16.0 years. About 57.0% of sexually active persons reported using condom during the last intercourse and only 26.5% (M > F, p = 0.017) admitted always using it. Females were found to become sexually active earlier, had more partners in the previous six months and less frequently used condoms. No case of N. gonorrhoeae infection was identified, while 8 males and 13 females were positive for C. trachomatis, with a prevalence rate among sexually active students of 2.4% (IC 95%:1.0–4.8) and 1.9% (IC 95%:1.0–3.3) respectively. The factors significantly associated with an increased risk of Chlamydial infection were the inconsistent condom use (p = 0.029) and a higher number of sexual partners during the previous six months (p = 0.013). Conclusion: A lower than expected prevalence of C. trachomatis infection was observed among sexually active adolescents in Northern Italy. Study conducted with scientific and logistic support from Copan S.p.A. and Siemens Healthcare Diagnostic S.p.A.